SculpTTura : Mostra nr. 142 - Pozzati, Concetto (Verona : Studio La Città, 1989)
Fontana, Lucio ; Vedova, Emilio ; Scanavino, Emilio ; Pozzatti, Concetto ; Paolini, Giulio ; Pistoletto, Michelangelo ; Gilardi, Piero ; Plessi, Fabrizio ; Paladino, Mimmo ; Ceccobelli, Bruno ; Garutti, Sergio ; Fogli, Andrea
SculpTTura : Mostra nr. 142, Studio La Città, Verona, 12 maggio 1989
Italiaans
kunstcatalogus